The value of susceptibility weighted imaging for immediate assessing the hyperacute outcome of MRgFUS ablation for uterine fibroids: a preliminary study - Yaoqu Huang; Shouguo Zhou; Yinghua Su; Zhuochao Pang; Shihua Cai (International Journal of Hyperthermia)
Purpose To investigate the value of susceptibility weighted imaging (SWI) for assessing the hyperacute outcome of ablation of uterine fibroids immediately after magnetic resonance-guided focused ultrasound (MRgFUS) treatment.Methods This retrospective imaging study included patients who underwent SWI and contrast-enhanced (CE) MR within 15 min of MRgFUS ablation for uterine fibroids. Two readers independently assessed the SWI features of ablative lesions and their association with the non-perfused volume (NPV) ratio. The intraclass correlation coefficient (ICC) and diagnostic value of SWI findings were calculated.Results A total of 27 uterine fibroids from 21 participants (mean age 40.1 ± 7.2 years) were analyzed. 51.9% (14/27) leiomyomas had NPV ratio ≥90%. In post-ablation SWI images, the interobserver ICC for the relative signal intensity and hypointense peripheral rim were 0.613 and 0.843, respectively (both p < .001). There was a significant difference in the prevalence of hypointense peripheral rim in leiomyomas with NPV ratio ≥90% and < 90% (p < .01), while the prevalence of relative signal intensity showed no significant difference (p > .05). When using the complete hypointense peripheral rim as a diagnostic criterion to identify NPV ratio ≥ 90%, readers 1 and 2 showed diagnostic sensitivity, specificity, and accuracy of 85.7%, 76.9%, 81.5%, and 78.6%, 76.9%, 77.8%, respectively.Conclusion Identifying a complete hypointense peripheral rim on SWI may be a potential imaging marker for assessing the hyperacute outcome of uterine fibroids ablation by MRgFUS, specifically in determining whether the NPV ratio is ≥90%.